2022
DOI: 10.21577/0103-5053.20220073
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Commercially Available Turmeric for Use in Pharmaceutical Products and Food Supplements

Abstract: We addressed some physicochemical and biological differences in commercial turmeric, acquired from both handling pharmacies and stores selling natural products for quality assessment. For this, it was determined the melting point, antioxidant activity by 2,2-diphenyl-1-picryl-hydrazylhydrate (DPPH), antimicrobial activity via the agar disk-diffusion assay, metallic contaminants by X-ray fluorescence with energy dispersion (EDXRF), spectral behaviors by Fourier transform infrared (FTIR) and ultraviolet-visible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…The peak at 1152 cm −1 shows the result of the C-O-C stretching [66]. The peak appears at 1026 cm −1 , and Boscariol et al reported that the peak is caused by the presence of the ether functional group (C-O-C) [67]. The peak at 961 cm −1 was identified by El-Nahhal et al as a benzoate trans-CH vibration, which could cause this peak [68].…”
Section: Ftir Spectrummentioning
confidence: 96%
“…The peak at 1152 cm −1 shows the result of the C-O-C stretching [66]. The peak appears at 1026 cm −1 , and Boscariol et al reported that the peak is caused by the presence of the ether functional group (C-O-C) [67]. The peak at 961 cm −1 was identified by El-Nahhal et al as a benzoate trans-CH vibration, which could cause this peak [68].…”
Section: Ftir Spectrummentioning
confidence: 96%